PENGEMBANGAN MEDIA PEMBELAJARAN E-BOOK BERBASIS MULTIMEDIA INTERAKTIF UNTUK MELATIH KEMAMPUAN MEMBACA PADA PESERTA DIDIK KELAS IV DI SEKOLAH DASAR - Ruhe Restiani; Sundawati Tisnasari; Rina; Tatu Hilaliyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
This research is motivated by the lack of use of learning media in teaching and learning activities. This study aims to develop an interesting learning media by utilizing technological tools. This research uses research and development research and development (R & D) methods. The resulting media is an interactive multimedia-based e-book. This research was conducted at SDN 2 Bayah Barat with the research subject, namely the fourth grade students, totaling 28 people. The researcher uses a research method that refers to the Borg and Gall development model that has been modified by Sugiyono. The procedure used by the researcher is, only 6 stages. To test the feasibility of the media developed by the researchers, the researchers first validated it with a team of media experts, material experts, and linguists. Based on the results of data analysis from the 6 validators, the interactive multimedia-based e-book media developed by the researcher is included in the